A Streptomyces venezuelae cell-free toolkit for synthetic biology - Moore,SJ; Lai,H-E; Chee,S-M; Toh,M; Coode,S; Chengan,K; Capel,P; Corre,C; de,los Santos ELC; Freemont,PS (ACS Synthetic Biology, 2021)
Prokaryotic cell-free coupled transcription–translation (TX-TL) systems are emerging as a powerful tool to examine natural product biosynthetic pathways in a test tube. The key advantages of this approach are the reduced experimental time scales and controlled reaction conditions. To realize this potential, it is essential to develop specialized cell-free systems in organisms enriched for biosynthetic gene clusters. This requires strong protein production and well-characterized synthetic biology tools. The Streptomyces genus is a major source of natural products. To study enzymes and pathways from Streptomyces, we originally developed a homologous Streptomyces cell-free system to provide a native protein folding environment, a high G+C (%) tRNA pool, and an active background metabolism. However, our initial yields were low (36 μg/mL) and showed a high level of batch-to-batch variation. Here, we present an updated high-yield and robust Streptomyces TX-TL protocol, reaching up to yields of 266 μg/mL of expressed recombinant protein. To complement this, we rapidly characterize a range of DNA parts with different reporters, express high G+C (%) biosynthetic genes, and demonstrate an initial proof of concept for combined transcription, translation, and biosynthesis of Streptomyces metabolic pathways in a single “one-pot” reaction.